Kinetics of Neutralizing Antibodies in Patients Naturally Infected by H5N1 Virus - Simmons, Cameron (2018)
BACKGROUND: Little is known about the kinetics of anti-H5 neutralizing antibodies in naturally H5N1-infected patients with severe clinical illness or asymptomatic infection. METHODS: Using H5N1 microneutralisation (MN) and H5-pseudotype particle-based microneutralisation assays (H5pp) we analyzed sera sequentially obtained from 11 severely ill patients diagnosed by RT-PCR (follow-up range 1-139 weeks of disease onset) and 31 asymptomatically infected individuals detected in a sero-epidemiological study after exposure to H5N1 virus (follow-up range: 1-2 month-11 months after exposure). RESULTS: Of 44 sera from 11 patients with H5N1 disease, 70% tested positive by MN (antibody titre > or = 80) after 2 weeks and 100% were positive by 3 weeks after disease onset. The geometric mean MN titers in severely ill patients were 540 at 1-2 months and 173 at 10-12 months and thus were higher than the titers from asymptomatic individuals (149 at 1-2 months, 62.2 at 10-12 months). Fractional polynomial regression analysis demonstrated that in all severely ill patients, positive titers persisted beyond 2 years of disease onset, while 10 of 23 sera collected 10-11 months after exposure in asymptomatically infected individuals tested negative. CONCLUSIONS: Our results indicate that people with asymptomatic H5N1 infection have lower H5N1 antibody titres compared to those with severe illness and that in many asymptomatically infected patients the antibody titer decreased to levels below the threshold of positivity within one year. These data are essential for the design and interpretation of sero-epidemiological studies.